Yusuf Qardhawi’s Thought about Zakat Shares - Navis Yusrizal; Bagas Wirya Sasmita (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2022)
One of the significant works in the field of zakat and which has become a general reference in the Islamic world, is Fiqh al-Zakah by Yusuf Qardhawi, zakat which is synonymous with only traditional practices which Yusuf Qardhawi transitioned by creating a new chapter, namely zakat on shares. This study aims to find out how Yusuf Qardhawi's opinion regarding the distribution of zakat shares. This type of research is library research, and the nature of the research is descriptive. Yusuf Qardhawi expressed two opinions regarding the issuance of zakat on shares, namely zakat on shares based on the type of company that issued it and zakat on shares is seen as the same as merchandise, according to Yusuf Qardhawi if the company is a pure industrial company, it means that it does not carry out trading activities such as hotel companies, travel agencies and transportation public. The shares are not obliged to be zakat, as for companies that carry out trading, their shares are obliged to be zakat.